2016
DOI: 10.1590/1414-431x20155043
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin attenuates the growth of HO-8910 ovarian cancer cells through the ERK pathway

Abstract: Ovarian cancer is one of the most common causes of death from gynecologic tumors and is an important public health issue. Ghrelin is a recently discovered bioactive peptide that acts as a natural endogenous ligand of the growth hormone secretagogue receptor (GHSR). Several studies have identified the protective effects of ghrelin on the mammalian reproductive system. However, little research has been done on the effects of ghrelin on ovarian cancer cells, and the underlying mechanisms of these effects. We soug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 18 publications
1
21
1
Order By: Relevance
“…It has been reported that ghrelin promotes prostate cancer cell proliferation and oral tumor cell proliferation through the regulation of glucose metabolism . However, ghrelin also inhibits cancer cell proliferation . Lin and Hsiao suggested that these discrepancies might be partially due to the ghrelin concentrations used to treat cancer cell lines .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ghrelin promotes prostate cancer cell proliferation and oral tumor cell proliferation through the regulation of glucose metabolism . However, ghrelin also inhibits cancer cell proliferation . Lin and Hsiao suggested that these discrepancies might be partially due to the ghrelin concentrations used to treat cancer cell lines .…”
Section: Discussionmentioning
confidence: 99%
“…In squamous cell carcinoma cells, MEK/ERK signaling has been demonstrated to support cell survival by inducing the anti-apoptotic protein Bcl-2 (28). Previous studies have shown that alteration of the MEK/ERK pathway is also strongly implicated in ovarian cancer pathogenesis (29)(30)(31)(32)(33)(34)(35)(36)(37). Al-Ayoubi et al (38) reported that signaling via the MEK/ERK pathway helps cells escape anoikis and maintain anchorage-independent growth in several ovarian cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that MAPKs (jNK1/2, ERK1/2, and p38) are involved in the growth, migration, and alterations in MMPs activity (24,25) in various cancers including lung, prostate, colorectal and ovarian cancer (26)(27)(28)(29)(30). Furthermore, the ERK signaling pathway in addition to the p38 signaling pathway may regulate numerous factors that are associated with cancer progression and poor prognosis in NSCLC (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%